2009
DOI: 10.1016/j.whi.2009.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders Among Low-Income Women and Unintended Pregnancies

Abstract: Research Question-Prevalence of both unintended pregnancy and psychiatric disorder in pregnancy is high and each is associated with compromised birth outcomes and challenges in childrearing. This study examines the relationship between mental illness and unintended pregnancy in seeking to improve the care provided to women and our ability to minimize the number of children born unwanted and ill-cared for.Methods-The sample consisted of 744 pregnant WIC participants with a stratified enrollment design by reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 57 publications
2
20
1
Order By: Relevance
“…In addition to contraceptive use, we are also currently examining the role of sexual behavior, including frequency of sexual activity and sexual partnerships, as additional mechanisms that may link mental health symptoms to pregnancy risk. While young women, including those wishing to avoid pregnancy, may have a variety of reasons for having more or less sex or for not using contraception (and indeed contraceptive nonuse is not uncommon (Frost & Darroch, 2008; Kost et al, 2008; Mosher & Jones, 2010; Trussell & Vaughn, 1999), our collective research suggests that mental health may be one factor which shapes women's family planning behaviors and outcomes. Among our adolescent women wishing to avoid pregnancy, those with moderate/severe mental health symptoms were at increased risk of behaviors that can lead to unintended pregnancy and for unintended pregnancy itself.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to contraceptive use, we are also currently examining the role of sexual behavior, including frequency of sexual activity and sexual partnerships, as additional mechanisms that may link mental health symptoms to pregnancy risk. While young women, including those wishing to avoid pregnancy, may have a variety of reasons for having more or less sex or for not using contraception (and indeed contraceptive nonuse is not uncommon (Frost & Darroch, 2008; Kost et al, 2008; Mosher & Jones, 2010; Trussell & Vaughn, 1999), our collective research suggests that mental health may be one factor which shapes women's family planning behaviors and outcomes. Among our adolescent women wishing to avoid pregnancy, those with moderate/severe mental health symptoms were at increased risk of behaviors that can lead to unintended pregnancy and for unintended pregnancy itself.…”
Section: Discussionmentioning
confidence: 90%
“…Given that inadequate contraceptive use accounts for 90% of the estimated 3.2 million annual U.S. unintended pregnancies, contraceptive (and sexual risk) behavior is indeed a primary mediating factor of unintended pregnancy (Finer & Henshaw, 2006; Kost et al, 2008; Trussell & Vaughn, 1999). Thus, research describing a link between mental health symptoms and family planning behaviors has been an important scientific contribution, one that appears to have theoretical validity.…”
Section: Introductionmentioning
confidence: 99%
“…Findings in the literature indicate that women with any psychiatric disorder are not more likely to have undesired pregnancy, compared with healthy ones 19,20 . They experience more often poverty, divorce, partner abuse and negative life events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not found an association between unplanned pregnancy and anxiety (Sayil et al, 2006; Tenkku et al, 2009), but are limited by retrospective (postpartum) assessment of pregnancy planning (Sayil et al, 2006) or inconsistent assessment of pregnancy planning (Tenkku et al, 2009) that can bias results (Santelli et al, 2009). …”
Section: Introductionmentioning
confidence: 99%